Prussian blue positive electrode material and preparation method thereof
By slowly melting ferrous salt and sodium ferrocyanide ice phase using the freezing point characteristics of alcohol solvents under low temperature environments, the coordination water and vacancy problems in the preparation of Prussian blue positive electrode materials are solved, forming nano-scale materials, and cycling stability is improved and multiplying capability.
Patent Information
- Application Number
- CN202411574256.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
AI Technical Summary
The existing Prussian blue positive electrode material preparation process is prone to generate coordination water and Fe(CN)6 vacancy, which destroys the integrity of the material structure, leads to collapse of the frame structure, slows down the Na+ transmission rate, affecting the material's cycle stability and magnification ability.
By utilizing the freezing point characteristics of alcohol solvents under low temperature environments, the frozen ferrous salt and sodium ferrocyanide ice phase slowly melt and a precipitation reaction occurs, reducing the precipitation rate and reducing the introduction of coordination water to form nano-scale Prussia Blue material.
A nano-scale Prussian blue cathode material with low coordination water and high initial specific capacity is achieved, which improves the cyclic stability and magnification capabilities of the material, and enhances the contact and ion migration channels with the electrolyte.
Smart Images

Figure CN119430227A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and particularly relates to a Prussian blue positive electrode material and a preparation method thereof. Background Art
[0002] With the development of large-scale energy storage systems (ESS), new opportunities have been brought about for long-life, high-capacity, low-cost, and environmentally friendly rechargeable batteries. Considering cycle life, operating conditions, safety, cost, and resource availability, sodium-ion batteries (SIBs) have become a strong competitor for the next generation of large-scale energy storage due to their low cost, abundant resource reserves, wide distribution, and high energy density.
[0003] Generally speaking, cathode materials are a key factor in developing high-performance batteries. Prussian blue (PB) and Prussian blue analogs (PBAs) cathode materials have open three-dimensional frameworks and large pore channels that can support the insertion / extraction of sodium ions. As energy storage materials, they have high specific capacity and fast ion transfer efficiency. They are a type of cathode material with great prospects. The preparation methods of Prussian blue materials mainly include chemical precipitation, hydrothermal, ball milling, electrochemical deposition, etc. Among them, the chemical precipitation method is prepared by precipitation reaction of ferrocyanide and transition metal salt solution. The process is simple, the synthesis process is safe and non-toxic, and it can be used for large-scale industrial production. However, it is inevitable that this method has problems such as the easy generation of coordinated water and Fe(CN)6 vacancies in the framework, which destroys the integrity of the material structure, thereby leading to the collapse of the Prussian blue framework structure during the cycle, and then causing Na + The transmission rate slows down, affecting the cycle stability and rate capability of the Prussian blue material.
[0004] In view of this, the use of chelating agents and element doping are currently commonly used improvement methods, but this will increase the complexity and cost of the process. Therefore, it is particularly important to develop a Prussian blue cathode material with low cost, high safety and excellent electrochemical performance to solve the above problems. Summary of the invention
[0005] The present invention aims to overcome the problem that the prior art process for preparing Prussian blue cathode materials easily produces coordinated water and Fe(CN)6 vacancies, which destroys the integrity of the material structure, thus leading to the collapse of the Prussian blue framework structure during the cycle, and thus causing Na + The transmission rate slows down, affecting the cycle stability and rate capability of the Prussian blue material. A Prussian blue positive electrode material and a preparation method thereof are provided.
[0006] To achieve the above-mentioned purpose, the present invention is implemented by the following technical solutions: A method for preparing a Prussian blue positive electrode material comprises the following steps: (S.1) Mix ferrous salt and reducing agent evenly and dissolve in deionized water to form solution A; Dissolve sodium ferrocyanide in deionized water to form solution B; The reducing agent and the surfactant are mixed uniformly and dissolved in an alcohol solvent to form a solution C; (S.2) freezing the solution A and solution B formed in step (S.1) to obtain ice phase A and ice phase B respectively; refrigerating the solution C formed in step (S.1) to obtain refrigerated solution C; (S.3) placing the ice phase A and ice phase B obtained in step (S.2) in a low temperature container and adding a refrigerated solution C, until the ice phase A and ice phase B are completely melted, collecting the Prussian blue particles and centrifuging and drying them to obtain the Prussian blue positive electrode material I-PB.
[0007] Under normal conditions, the freezing point of salt solution is between -20 and 0 ℃. When it is at -20 ℃, it is basically frozen. If it is transferred to an environment with a temperature above the freezing point of the solution or directly contacts with low freezing point alcohol solvents, it will undergo a phase change and gradually melt into liquid. The direction of heat transfer in the former is from the environment to the ice and its interior, while the latter releases heat from the ice to the external environment.
[0008] Obviously, the latter has a more slowing effect on ice melting and the resulting ion migration, providing an improved preparation method for the synthesis of Prussian blue with a larger solubility product.
[0009] The present invention utilizes the freezing point characteristics of the alcohol solvent to slowly melt the frozen ferrous salt and sodium ferrocyanide ice phases in a low temperature environment and cause a precipitation reaction. Specifically, the ferrous salt and sodium ferrocyanide required for the double iron method are dissolved to form a uniform solution, and then frozen to obtain ice phase A and ice phase B; the alcohol solvent and a certain amount of surfactant and reducing agent are mixed and dissolved uniformly and then refrigerated to obtain a refrigerated solution C; finally, the ice phase A and ice phase B are placed in a container in a low temperature environment, and the refrigerated solution C is poured therein, and the two ice phases are slowly melted until the reaction is complete in the refrigerated solution C, thereby obtaining a nano-scale Prussian blue positive electrode material I-PB with low coordinated water and high initial specific capacity.
[0010] The present invention utilizes the temperature difference (T) formed between the alcohol solvent which is still liquid at low temperature and the reactant which is solidified into ice state when they come into contact with each other at an ambient temperature of -20°C. 冰 >T 环境 ), and because of the difference in hydrogen bonding forces between alcohol-water and water-water, the alcohol solvent will destroy the ordered water molecule structure in the ice. Therefore, the ice phase under low temperature conditions can slowly melt under the joint action of the two, gradually releasing ferrous iron and ferrocyanide ions, reducing the precipitation rate.
[0011] In addition, the present invention utilizes the dual effects of the low dielectric constant of the alcohol solvent and the limited crystal size at low temperature to form nano-scale Prussian blue, so that the surface area of the material is increased to a certain extent, thereby having more contact with the electrolyte and ion migration channels.
[0012] In addition, the present invention utilizes the difference in solubility of the reactants between alcohol solvent and water, so that the solution formed by ice during the phase change process can precipitate trace solutes. As the water content in the entire reaction system gradually increases, the solutes will reach a dissolution equilibrium between the two solvents within a certain period of time. Therefore, the entire process can combine the reactant particles at a lower rate, making the nucleation and growth of Prussian blue slower and reducing the number of Fe(CN)6 vacancies.
[0013] In addition, the present invention also utilizes the difference in binding energy between alcohol solvent and water and coordinated metal ions, so that the introduction of coordinated water is reduced during the binding process of ferrous and ferrocyanide ions, which is beneficial for the material to have more sodium storage sites and capacity improvement during the charge and discharge process.
[0014] Preferably, the ferrous salt in step (S.1) is any one or more of ferrous sulfate heptahydrate, ferrous chloride tetrahydrate, ferrous nitrate hexahydrate and ferrous acetate.
[0015] Preferably, the reducing agent in step (S.1) is any one of ascorbic acid and hydroquinone, or a combination of the two.
[0016] The above-mentioned type of reducing agent has the excellent characteristics of strong reducing ability, mild reaction conditions, good stability and easy separation and recovery, which helps to improve the crystallinity and purity of Prussian blue and further improve its electrochemical performance.
[0017] Preferably, the alcohol solvent in step (S.1) is any one or more combinations of anhydrous ethanol, ethylene glycol and anhydrous methanol.
[0018] Preferably, the molar ratio of the ferrous salt to the reducing agent in step (S.1) is 1-1.7: 0.5-1.
[0019] Preferably, the concentration of solution B in step (S.1) is 0.1-1 mmol / mL.
[0020] Preferably, the surfactant in step (S.1) is any one or more combinations of polyethylene glycol, polyoxyethylene sorbitan fatty acid ester, polyvinyl pyrrolidone, and polyoxyethylene fatty acid ester.
[0021] The above-mentioned types of surfactants help to reduce the interfacial tension between the electrode material and the electrolyte and promote the uniform distribution of the electrolyte. Thereby improving the wettability of the Prussian blue cathode material, allowing the electrolyte to better penetrate into the material, thereby improving the performance of the battery. At the same time, polyvinyl pyrrolidone surfactants also help to stabilize the electrode structure, effectively preventing the structure of the Prussian blue cathode material from being destroyed, thereby extending the service life of the battery. In addition, by adding an appropriate amount of surfactant, the surface morphology and pore structure of the Prussian blue cathode material can be regulated, increasing the contact area between the electrode and the electrolyte, and helping to increase the charge transfer rate, thereby improving the charge and discharge performance and rate performance of the battery. Further improve the specific capacity and cycle stability of the Prussian blue cathode material.
[0022] Preferably, the solid-liquid ratio of the reducing agent, surfactant and alcohol solvent in step (S.1) is 0.5-1.5:0.75-1.25:100-200 g / g / mL.
[0023] Preferably, the freezing temperature of the freezing process in step (S.2) is -20~-40°C, and the freezing time is 12~24h; the refrigeration temperature of the refrigeration process is -20~-40°C, and the refrigeration time is 5~15h.
[0024] Preferably, in step (S.3), ice phase A and ice phase B are placed in a low temperature environment of -30 to -10 °C.
[0025] Ice phase A and ice phase B under low temperature conditions can melt slowly, thereby gradually releasing ferrous iron and ferrocyanide ions, which helps to reduce the precipitation rate.
[0026] The Prussian blue positive electrode material is prepared by the method for preparing the Prussian blue positive electrode material as described above.
[0027] Therefore, the present invention has the following beneficial effects: (1) The present invention utilizes the temperature difference (T) between the alcohol solvent which is still liquid at low temperature and the reactant which is solidified into ice when they come into contact with each other at an ambient temperature of -20°C. 冰 >T 环境 ), and because of the difference in hydrogen bonding forces between alcohol-water and water-water, the alcohol solvent will destroy the orderly water molecular structure in the ice. Therefore, the ice phase under low temperature conditions can slowly melt under the combined action of the two to gradually release ferrous iron and ferrocyanide ions, reducing the precipitation rate; (2) The present invention utilizes the dual effects of the low dielectric constant of the alcohol solvent and the limited crystal size at low temperature to form nano-scale Prussian blue, so that the surface area of the material is increased to a certain extent, thereby enabling more contact with the electrolyte and ion migration channels; (3) The present invention utilizes the difference in solubility of the reactants between alcohol solvent and water, so that the solution formed by ice during the phase change process can precipitate a trace amount of solute. As the water content in the entire reaction system gradually increases, the solute will reach a dissolution equilibrium between the two solvents within a certain period of time. Therefore, the entire process can combine the reactant particles at a lower rate, resulting in slower nucleation and growth of Prussian blue, thereby reducing the number of vacancies in Fe(CN)6. (4) The present invention also utilizes the difference in binding energy between alcohol solvent and water and coordinated metal ions to reduce the introduction of coordinated water during the binding process of ferrous and ferrocyanide ions, which is beneficial for the material to have more sodium storage sites and increased capacity during the charge and discharge process. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the design of the preparation device for Prussian blue positive electrode material.
[0029] Figure 2 1 and 2 are XRD diagrams of the Prussian blue positive electrode material I-PB1 in Example 1 and the Prussian blue positive electrode material C-PB in Comparative Example 1.
[0030] Figure 3 TG diagrams of the Prussian blue positive electrode material I-PB1 in Example 1 and the Prussian blue positive electrode material C-PB in Comparative Example 1.
[0031] Figure 4 The charge and discharge curves of the button half-cell assembled with the Prussian blue positive electrode material I-PB1 in Example 1 at various current densities.
[0032] Figure 5 The charge and discharge curves of the button half-cell assembled with the Prussian blue positive electrode material C-PB in Comparative Example 1 at various current densities.
[0033] Figure 6 The button-type half-cells assembled with different cathode materials are shown in Figure 1 at 10 mA g -1 The charge and discharge performance diagram below. DETAILED DESCRIPTION
[0034] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments of the specification. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0035] Example 1 This embodiment provides a Prussian blue positive electrode material and a preparation method thereof.
[0036] A method for preparing a Prussian blue positive electrode material comprises the following steps: (S.1) Dissolve 9 mmol of ferrous sulfate heptahydrate (FeSO4•7H2O) and 0.9 g of ascorbic acid (Vc) in 90 mL of deionized water to form a uniform solution A; Dissolve 9 mmol of sodium ferrocyanide in 90 mL of deionized water to form a homogeneous solution B; Mix 1 g of ascorbic acid and 1 g of polyvinylpyrrolidone (PVP) and dissolve them in 120 mL of anhydrous ethanol to form a uniform solution C; (S.2) Freezing the solution A and solution B formed in step (S.1) at -20°C for 12 hours to obtain ice phase A and ice phase B, respectively; Refrigerate the solution C formed in step (S.1) at -20°C for 5 h to obtain a refrigerated solution C; (S.3) The ice phase A and ice phase B obtained in step (S.2) are placed in a container at a low temperature of -20°C, and then the refrigerated solution C is poured in so that the refrigerated solution C submerges the ice phase A and ice phase B to a certain height; as the ice phase A and ice phase B slowly melt and react, Prussian blue particles are gradually produced; when the ice phase A and ice phase B are completely melted, the Prussian blue particles are collected and centrifuged and dried to obtain a Prussian blue positive electrode material, which is recorded as I-PB1.
[0037] The Prussian blue positive electrode material I-PB1 prepared by the preparation method of the Prussian blue positive electrode material as described above. Figure 1 shown.
[0038] Example 2 The difference between this embodiment and embodiment 1 is that: A method for preparing a Prussian blue positive electrode material, wherein ethylene glycol is used to replace anhydrous ethanol in step (S.1), and the rest is the same as in Example 1. Finally, a Prussian blue positive electrode material is obtained, which is recorded as I-PB2.
[0039] The Prussian blue positive electrode material I-PB2 is prepared by the preparation method of the Prussian blue positive electrode material as described above.
[0040] Example 3 The difference between this embodiment and embodiment 1 is that: A method for preparing a Prussian blue positive electrode material, wherein anhydrous methanol is used to replace anhydrous ethanol in step (S.1). The rest is the same as in Example 1. Finally, a Prussian blue positive electrode material is obtained, which is recorded as I-PB3.
[0041] The Prussian blue positive electrode material I-PB3 is prepared by the preparation method of the Prussian blue positive electrode material as described above.
[0042] Example 4 The difference between this embodiment and embodiment 1 is that: A method for preparing a Prussian blue positive electrode material, wherein in step (S.1), 15 mmol of ferrous sulfate heptahydrate and 1.2 g of ascorbic acid are dissolved in 90 mL of deionized water to form a uniform solution A; Dissolve 45 mmol sodium ferrocyanide in 90 mL deionized water to form a homogeneous solution B; 0.5 g ascorbic acid and 0.75 g polyvinyl pyrrolidone were mixed and dissolved in 100 mL anhydrous ethanol to form a uniform solution C; In step (S.2), the solution A and solution B formed in step (S.1) are respectively frozen at -30°C for 18 h to obtain ice phase A and ice phase B, respectively; Refrigerate the solution C formed in step (S.1) at -30°C for 10 h to obtain a refrigerated solution C; In step (S.3), the ice phase A and the ice phase B obtained in step (S.2) are placed in a container at a low temperature of -30°C; finally, a Prussian blue positive electrode material is obtained, which is recorded as I-PB4.
[0043] The Prussian blue positive electrode material I-PB4 is prepared by the preparation method of the Prussian blue positive electrode material as described above.
[0044] Example 5 The difference between this embodiment and embodiment 1 is that: A method for preparing a Prussian blue positive electrode material, wherein in step (S.1), 24 mmol of ferrous sulfate heptahydrate and 2.5 g of ascorbic acid are dissolved in 90 mL of deionized water to form a uniform solution A; Dissolve 90 mmol of sodium ferrocyanide in 90 mL of deionized water to form a homogeneous solution B; 1.5 g of ascorbic acid and 1.25 g of polyvinyl pyrrolidone were mixed and dissolved in 200 mL of anhydrous ethanol to form a uniform solution C; In step (S.2), the solution A and solution B formed in step (S.1) are respectively frozen at -40°C for 24 hours to obtain ice phase A and ice phase B, respectively; Refrigerate the solution C formed in step (S.1) at -40°C for 15 h to obtain a refrigerated solution C; In step (S.3), the ice phase A and the ice phase B obtained in step (S.2) are placed in a container at a low temperature of -40°C; finally, a Prussian blue positive electrode material is obtained, which is recorded as I-PB5.
[0045] The Prussian blue positive electrode material I-PB5 is prepared by the preparation method of the Prussian blue positive electrode material as described above.
[0046] Example 6
Cathode preparation and battery assembly
[0047] Comparative Example 1 The difference between this comparative example and Example 1 is: A method for preparing a Prussian blue positive electrode material, wherein step (S.1) is the same as in Example 1. In step (S.2), solution A and solution B are not subjected to freezing treatment, and solution C is not subjected to refrigeration treatment. That is, step (S.2) is replaced by: solution A and solution B formed in step (S.1) are simultaneously dripped into solution C dropwise and continuously stirred, and then the obtained blue precipitate is aged, centrifuged, dried and collected to obtain a Prussian blue positive electrode material, recorded as C-PB.
[0048] The Prussian blue positive electrode material C-PB is prepared by the preparation method of the Prussian blue positive electrode material as described above.
[0049] Comparative Example 2 The difference between this comparative example and Example 1 is: A method for preparing a Prussian blue positive electrode material, wherein in step (S.1), deionized water is used to replace anhydrous ethanol. The rest is the same as in Example 1. However, in step (S.2), solution C forms an ice phase C after refrigeration treatment, that is, solution A, solution B, and solution C are all in a frozen state. In step (S.3), ice phase A and ice phase B do not melt. In the end, the Prussian blue positive electrode material cannot be obtained.
[0050]
Performance testing and analysis
[0051] from Figure 2 From the analysis, it can be seen that the sample prepared by the process preparation method in Example 1 is determined to be the Prussian blue positive electrode material I-PB1, which clearly shows characteristic peaks such as 200, 220, and 400. It also shows that the Prussian blue positive electrode material I-PB1 and the Prussian blue positive electrode material C-PB prepared in Comparative Example 1 are both cubic phases with better crystal morphology.
[0052] Prussian blue positive electrode material I-PB1 and Prussian blue positive electrode material C-PB were prepared according to the methods in Example 1 and Comparative Example 1, and TG tests were performed on them. The TG graphs of the Prussian blue positive electrode material I-PB1 in Example 1 and the Prussian blue positive electrode material C-PB in Comparative Example 1 are as follows: Figure 3 shown.
[0053] from Figure 3 From the analysis, it can be seen that the TG curve shows the coordinated water content of the two samples (210-300 ℃), and the crystallization water content of the Prussian blue positive electrode material I-PB1 and the Prussian blue positive electrode material C-PB are 7.26% and 6.76%, respectively; the TG curves of the two are similar before 300 ℃, which may be because the ice melting method in Example 1 is similar to the liquid dropping method in Comparative Example 1. The ferrocyanide and ferrous ions in the precipitation process will combine at a slow rate in a large amount of ethanol environment, and the coordinated water around the metal ions can be replaced by a certain amount of ethanol molecules; at the same time, because the entire reaction is carried out in a low temperature environment, the crystal growth is susceptible to certain temperature restrictions, and the migration rate of anions and cations generated by ice melting is also reduced, which is more conducive to the entire synthesis process towards a slow reaction rate and a low coordinated water content.
[0054] Prussian blue positive electrode material I-PB1 and Prussian blue positive electrode material C-PB were prepared according to the methods in Example 1 and Comparative Example 1, and then button-type half-cells were assembled according to the positive electrode preparation and battery assembly methods provided in Example 6, and the charge and discharge conditions of the button-type half-cell assembled with the Prussian blue positive electrode material I-PB1 at various current densities and the charge and discharge conditions of the button-type half-cell assembled with the Prussian blue positive electrode material C-PB at various current densities were tested. The charge and discharge curves of the button-type half-cell assembled with the Prussian blue positive electrode material I-PB1 at various current densities are shown in FIG. Figure 4 The charge and discharge curves of the button half-cell assembled with Prussian blue positive electrode material C-PB at various current densities are shown in Figure 5 shown.
[0055] from Figures 4 and 5 From the analysis, it can be seen that the charge and discharge curve platforms of Prussian blue positive electrode material I-PB1 and Prussian blue positive electrode material C-PB at different current densities are both two, but it can be clearly seen that most of the capacity contribution of Prussian blue positive electrode material I-PB1 during the charge and discharge process comes from high-spin iron sites, and it is better than Prussian blue positive electrode material C-PB, so that the overall charge and discharge curve is closer to a smooth single platform, which is conducive to the sodium-ion battery to obtain more stable electrochemical performance as a whole.
[0056] Prussian blue positive electrode material I-PB1, Prussian blue positive electrode material C-PB, Prussian blue positive electrode material I-PB2, and Prussian blue positive electrode material I-PB3 were prepared according to the methods in Examples 1 to 3 and Comparative Example 1, and then button half-cells were assembled according to the positive electrode preparation and battery assembly methods provided in Example 6, and the assembled button half-cells were tested at 10 mA g -1 Charge and discharge performance of button-type half-cells assembled with different cathode materials at 10 mA g -1 The charge and discharge performance diagram is as follows Figure 6 shown.
[0057] from Figure 6 The analysis shows that the button half-cell assembled with the Prussian blue cathode material I-PB1 prepared with anhydrous ethanol as the "melting agent" has a good conductivity at 10 mA g -1 The charge and discharge capacity can reach 148 mAh g -1 The button half-cells assembled from Prussian blue positive electrode materials I-PB2, I-PB3, and C-PB, respectively, were tested at 10 mA g -1 The charge and discharge capacity can reach 147 mAh g -1 , 146 mAh g -1 , 129 mAh g -1 It can be seen that the three types of alcohol solvents can melt ice at low temperatures to prepare nano-scale Prussian blue positive electrode materials with relatively excellent electrochemical performance, which are superior to the preparation method of co-precipitation at room temperature.
[0058] In summary, the present invention adopts an alcohol melting ice strategy to prepare a Prussian blue cathode material under a low temperature environment. Using an alcohol solvent as a substrate solution can effectively reduce the coordinated water introduced during the synthesis of Prussian blue and increase its sodium ion storage performance. At the same time, due to the lower dielectric constant of the alcohol solvent and the restriction of low temperature on crystal growth, the particle size of the Prussian blue cathode material can be reduced and its contact area with the electrolyte can be increased. Therefore, this process method provides a novel possibility for the low-temperature preparation of Prussian blue cathode materials and sodium ion batteries with better electrochemical performance.
[0059] The above description is only a detailed description of the preferred embodiments and principles of the present invention. For ordinary technicians in this field, according to the ideas provided by the present invention, there will be changes in the specific implementation methods, and these changes should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a Prussian blue positive electrode material, characterized in that: The following steps are involved: (S.1) Mix ferrous salt and reducing agent evenly and dissolve in deionized water to form solution A; Dissolve sodium ferrocyanide in deionized water to form solution B; The reducing agent and the surfactant are mixed uniformly and dissolved in an alcohol solvent to form a solution C; (S.2) freezing the solution A and solution B formed in step (S.1) to obtain ice phase A and ice phase B respectively; refrigerating the solution C formed in step (S.1) to obtain refrigerated solution C; (S.3) placing the ice phase A and ice phase B obtained in step (S.2) in a low temperature container and adding a refrigerated solution C, until the ice phase A and ice phase B are completely melted, collecting the Prussian blue particles and centrifuging and drying them to obtain the Prussian blue positive electrode material I-PB.
2. The method for preparing a Prussian blue positive electrode material according to claim 1, characterized in that: The ferrous salt in step (S.1) is any one or more of ferrous sulfate heptahydrate, ferrous chloride tetrahydrate, ferrous nitrate hexahydrate and ferrous acetate.
3. The method for preparing a Prussian blue positive electrode material according to claim 1, characterized in that: The reducing agent in step (S.1) is any one of ascorbic acid and hydroquinone or a combination of the two; The alcohol solvent is any one or more combinations of anhydrous ethanol, ethylene glycol, and anhydrous methanol.
4. The method for preparing a Prussian blue positive electrode material according to claim 1, characterized in that: The molar ratio of the ferrous salt to the reducing agent in step (S.1) is 1-1.7: 0.5-1.
5. The method for preparing a Prussian blue positive electrode material according to claim 1, characterized in that: The concentration of solution B in step (S.1) is 0.1~1 mmol / mL.
6. The method for preparing a Prussian blue positive electrode material according to claim 1, characterized in that: The surfactant in step (S.1) is any one or more combinations of polyethylene glycol, polyoxyethylene sorbitan fatty acid ester, polyvinyl pyrrolidone, and polyoxyethylene fatty acid ester.
7. The method for preparing a Prussian blue positive electrode material according to claim 1, characterized in that: The solid-liquid ratio of the reducing agent, surfactant and alcohol solvent in step (S.1) is 0.5~1.5:0.75~1.25:100~200 g / g / mL.
8. The method for preparing a Prussian blue positive electrode material according to claim 1, characterized in that: The freezing temperature of the freezing process in step (S.2) is -20~-40°C, and the freezing time is 12~24 hours; the refrigeration temperature of the refrigeration process is -20~-40°C, and the refrigeration time is 5~15 hours.
9. The method for preparing a Prussian blue positive electrode material according to claim 1, characterized in that: In step (S.3), ice phase A and ice phase B are placed in a low temperature environment of -30~-10 ℃.
10. The Prussian blue positive electrode material prepared by the method for preparing a Prussian blue positive electrode material according to any one of claims 1 to 9.